New Alkaloids and Cytotoxic Principles from Sinomenium acutum - Cheng, Jing-Jy; Tsai, Tung-Hu; Lin, Lie-Chwen (Planta Medica, 2012)
Two new alkaloids, 2-demethyl-oxypalmatine (1) and 5-ethoxycarbonylsinoracutine (2), were isolated from the rhizomes of Sinomenium acutum, along with thirty-four known compounds. Cytotoxicity of the isolated compounds was examined for the MCF-7, H460, HT-29, and CEM human cancer cell lines. Dauriporphine (16), 6-O-demethylmenisporphine (17), bianfugecine (18), menisporphine (19), and 6-O-demethyldauriporphine (20) showed differential effects in their cytotoxic activity on the target cancer cell lines. Significant angiogenesis inhibitions of 16 and 19 were also observed.
Keywords: Sinomenium acutum; Menispermaceae; 2-demethyl-oxypalmatine; 5-ethoxycarbonylsinoracutine; cytotoxicity; angiogenesis